Sea Cucumber Intestinal Peptide Induces the Apoptosis of MCF-7 Cells by Inhibiting PI3K/AKT Pathway - Wei, Wei; Fan, Xiao-Man; Jia, Shao-Hui; Zhang, Xi-Ping; Zhang, Zhao; Zhang, Xue-Jun; Zhang, Jiu-Xun; Zhang, Ye-Wang (Frontiers in Nutrition, 2021)
Sea cucumbers are one of many marine echinoderm animals that contain valuable nutrients and medicinal compounds. The bioactive substances in sea cucumbers make them having promising biological and pharmacological properties, including antioxidant, antibacterial, and antitumor effects. In this study, Sea cucumber intestinal peptide (SCIP) is a small molecular oligopeptide (less than 1000 Da) extracted from sea cucumber intestines hydrolyzed by alkaline protease. The analysis of amino acid composition showed that hydrophobic amino acids and branched-chain amino acids were rich in SCIP. Nowadays, although increasing studies have revealed the biological functions of the sea cucumber active substances, there are few studies on the function of SCIP. Furthermore, due to the anticancer activity being an essential characteristic of sea cucumber active substances, we also investigated the anticancer potential and the underlying mechanism of SCIP in vivo and in vitro. The results indicate that SCIP inhibits the growth of MCF-7 tumor cells in zebrafish and increases the apoptosis of human breast cancer MCF-7 cells. Further mechanism studies confirm that SCIP promotes the expression of apoptosis-related proteins and thus promotes the breast cancer cells (MCF-7) apoptosis via inhibition of PI3K/AKT signal transduction pathway.